TREATMENT OF CRIMINAL ACTION OF RARE INTEREST INTEREST IN GUSTI NGURAH RAI AIRPORT - KADEK PUTRA PASTIKA (Kerta Dyatmika, 2020)
ABSTRACT This research is backed by the rise of rare wildlife smuggling through the airport line I Gusti Ngurah Rai where the endangered species itself is then traded so that some people commits smuggling actions to benefit him and can result in a rare wildlife smuggled, where endangered animals themselves are protected by Law No. 5 of 1990 on the conservation of natural resources and its ecosystem, then from the background was applied 2 problems of the problem is how the procedure of action against the criminal offenses of endangered animals by PT. Angkasa Pura at I Gusti Ngurah Rai airport? What are the efforts undertaken by PT Angkasa Pura to suppress the number of endangered ani mal smuggling crimes at I Gusti Ngurah Rai airport?This method of research method used is the empirical research method of empirical research in which the occurrence of rare wildlife smuggling protected by law number 5 of 1990 on the conservation of natur al resources and ecosys tems refers to the formulation of problems and is held from the objectives of legal research, then in this thesis research using the type of legal research empirical research empirical law is a legal research method that serves to se e the law in real sense and examine how it works legally in the community This research is descriptive where the research describes precisely the properties, symptoms with other symptoms in the community Key words: smuggling, endangered animals, violating law